Proceedings of the Thirty-Fifth Annual ACM Symposium on Theory of Computing 2003
DOI: 10.1145/780542.780608
|View full text |Cite
|
Sign up to set email alerts
|

A tight bound on approximating arbitrary metrics by tree metrics

Abstract: In this paper, we show that any n point metric space can be embedded into a distribution over dominating tree metrics such that the expected stretch of any edge is O(log n). This improves upon the result of Bartal who gave a bound of O(log n log log n). Moreover, our result is existentially tight; there exist metric spaces where any tree embedding must have distortion Ω(log n)-distortion. This problem lies at the heart of numerous approximation and online algorithms including ones for group Steiner tree, metri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
754
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 523 publications
(762 citation statements)
references
References 49 publications
6
754
0
Order By: Relevance
“…The leaves of T are the vertices in P , and the internal nodes are Steiner nodes. Fakcharoenphol, Rao and Talwar [11] have shown that for any metric (P, d) one can find a family of trees such that a randomly selected metric from the family has expected distortion of O(log n), which is also tight.…”
Section: Definition 1 (α-Hst [5]) a Rooted Weighted Tree H Is An α-Hmentioning
confidence: 98%
See 4 more Smart Citations
“…The leaves of T are the vertices in P , and the internal nodes are Steiner nodes. Fakcharoenphol, Rao and Talwar [11] have shown that for any metric (P, d) one can find a family of trees such that a randomly selected metric from the family has expected distortion of O(log n), which is also tight.…”
Section: Definition 1 (α-Hst [5]) a Rooted Weighted Tree H Is An α-Hmentioning
confidence: 98%
“…Review of The FRT Algorithm [11]. Without loss of generality, we assume that the smallest distance between any two vertices in P is 1 and the diameter of P is ∆.…”
Section: Definition 1 (α-Hst [5]) a Rooted Weighted Tree H Is An α-Hmentioning
confidence: 99%
See 3 more Smart Citations